Distúrbio de voz, estresse no trabalho e COVID-19 em professores: impactos em tempos de pandemia - Bonfim, Maria Madalena Ferreira do (2023)
Introduction: the connection between the presence of voice disorders and stress at work has been recorded in researches with teachers. It is believed that the Covid-19 pandemic has intensified this occurrence. Objective: to analyze the relations between the presence of voice disorder, stress at work and Covid-19 among teachers, when in a situation of teaching emergency remote classes, during the pandemic. Method: primary, observational cross-sectional study, carried out with teachers from both sexes and basic education in the public school system of São Paulo, during the Covid-19 pandemic. Teachers were selected through a convenience sample, using the Snowball Strategy, and were invited to respond, during the remote teaching period, to a webbased questionnaire, which could be completed using a cell phone or a computer with internet access. Covid-19 related data were collected and the teachers' vocal production conditions instruments (CPV-P) were applied to collect data regarding sociodemographic aspects, functional situation, Voice Disorder Screening Index (SIVD) to map the presence of symptoms and voice disorder (VD) and Job Stress Scale (JSS) to assess the dimensions of demand, control and social support, referring to the sources of stress in the psychosocial work environment. Data were analyzed through qualitative descriptive analyzes in frequency tables and quantitative analysis as median and quartiles. The Mann Whitney and Chi Square test were used to compare the groups, associate the symptoms of SIVD and the domains of JSS and COVID-19. The significance level adopted for the analyzes was 5%. Results: among the 118 teachers analyzed, 94.1% are women. A little more than half of them teach in Kindergarten (55.1%) and the majority (78.8%) have had the experience of teaching from home. About remote teaching, 80.7% taught classes in the school semester at the time of the survey. SIVD recorded the presence of voice disorders in 66.9% of the participants. The most reported symptoms were, always, dry throat (18.6%), tiredness when speaking (17.8%) and, in the same percentage, hoarseness and rough voice (14.4%). With regard to the JSS, in the demand domain, which represents any type of pressure of a psychic nature to perform a job, 52.5% of the participants have a high job demand. In the control domain, where the workers have the possibility to use their skills to perform the work and autonomy to make decisions, 56.8% have low control. For social support, which is social support in the work environment involving colleagues and different hierarchical levels, 58.5% of participants have low social support. Teachers who have a voice disorder are statistically older (p=0.049) and have high social support (p=0.043) with a report of Covid-19 manifesting symptoms. Conclusion: basic education teachers from the public school system in the city of São Paulo showed the presence of voice disorders, more common in older teachers, even in remote classes and conditions experienced during a pandemic. The four dimensions of the JSS did not present major differences, but it is noteworthy that passive work and high strain, harmful to health, when added together, reveal that teachers are in more noxious working conditions for the worker